Mapping the meaning of “Keadaan” in the news of DPR demonstrations demands: A natural semantic metalanguage study - Ni Kadek Devi Rahayu Padmayanti (Priviet Social Sciences Journal, 2025)
This study aims to describe the variations in the use of the word "keadaan" ("state") in news about the DPR's demands demonstration and to map its meaning categories based on the Natural Semantic Metalanguage (MSA) approach. This study uses a qualitative method with documentation techniques on online news texts containing the word "keadaan" ("state") and collected from various national news portals during the period of August–September 2025. The analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions based on the Natural Semantic Metalanguage theory of Wierzbicka and Goddard (2014). The results of the study found 20 words variations that represent five main categories of meaning of "keadaan" ("state"): stable and positive states, negative and chaotic states, states of density/mobility, psychological/emotional states, and uncertain states. The dominant semantic primes are PEOPLE, HAPPEN, and GOOD/BAD. This study confirms that the MSA approach is effective in explaining the meaning of state words in a simple but profound way, while at the same time shows that media language shapes socio political perceptions through lexical choices